Modelagem matemática na formação continuada: análise das concepções de professores em um curso de specialização - Silva, Marcelo Navarro da (2009)
This dissertation has as main aim analyze the conceptions of three teacher student of a specialization course at Mathematics Modelling, coordinated by Professor Rodney Carlos Bassanezi at a University in São Paulo, Brazil. The work also presents D Ambrosio s view (1993), (1997), (2001) of the concept and dimensions of the Ethnomathematics program. The considerations about Mathematics Modelling are supported by Biembengut & Hein (2002) and Bassanezi (2002), which links Mathematics Modelling and Semiotic. Presenting the proposals for the training of Mathematics teachers by Almeida & Dias (2007) and Day s (2001), we propose Modelling as an alternative to these training courses. We discuss the teacher training program proposed by Bassanezi, including the Modelling course offered in the UFABC. We discuss the ideas of Ponte (1992) and others on conceptions, teaching and learning processes, practices, processes of changing teachers conceptions. It is emphasized, too, the importance of qualitative research, as well the method used collecting data. In concluding, there is the presentation of the analysis of the data collected, based on teachers conceptions about Mathematics Modelling; which are classified in four categories